Sharpening the character of local wisdom in virtual communication in Indonesia - RISTIANI, I (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This article aims to analyze what characters emerge when someone communicates virtually and what must be done so that local wisdom is maintained by continuing to follow the era of rapid technological development. The conclusion of this article is to maintain the politeness of language as self-control in the embodiment of a civilized society. So it is necessary to understand the existing local wisdom that can become a tool in self-control when we think. It should always be filtered whether the opinions expressed have paid attention to aspects of wisdom, acceptance, generosity, approval, and sympathy for others.